2015
DOI: 10.1007/978-3-319-14618-8_8
|View full text |Cite
|
Sign up to set email alerts
|

Gelfand–Shilov Type Spaces Through Hermite Expansions

Abstract: Abstract. Gelfand-Shilov spaces of the type S α α (R d ) and α α (R d ) can be realized as sequence spaces by means of the Hermite representation Theorem. In this article we show that for a function, where 1 2 ≤ α ≤ β (resp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Proof. We use the Hermite functions It is known that Gelfand-Shilov spaces and their distribution duals can be identified by means of such series expansions, with characterizations in terms of the corresponding sequence spaces (see [14,15,38] and the references therein).…”
Section: Appendixmentioning
confidence: 99%
“…Proof. We use the Hermite functions It is known that Gelfand-Shilov spaces and their distribution duals can be identified by means of such series expansions, with characterizations in terms of the corresponding sequence spaces (see [14,15,38] and the references therein).…”
Section: Appendixmentioning
confidence: 99%
“…Gelfand-Shilov spaces and their ultradistribution duals, as well as the Schwartz space S and the tempered distributions S ′ , and L 2 , can be identified by means of such series expansions, with characterizations in terms of the corresponding sequence spaces (see [7,6,22,28]). Let…”
Section: Preliminariesmentioning
confidence: 99%
“…Gelfand-Shilov spaces and their distribution duals, as well as the Schwartz space S and the tempered distributions S ′ , can be identified by means of such series expansions, with characterizations in terms of the corresponding sequence spaces (see [4,5,16,20] [20,Theorem V.13] showed that the family of Hilbert sequence spaces…”
Section: Preliminariesmentioning
confidence: 99%